Effect of synthetic leu-enkephalin on the lipid profile in homeothermic animals under conditions of chronic cold stress - Mirnyy, Vladyslav; Moisieieva, Nataliia; Akhatova, Yuliia; Gorina, Olha (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):244